Panel Doctor System (PDS) for employee medical information system / Teh Boon Heng - Teh, Boon Heng (2002)
Panel Doctor System (PDS) is a distributed system developed for the companies to keep track and control the company expenses on the employees' medical expenses. Most of the companies have their own medical consultants that provide medical treatment to the employees of the company. It is one of the welfare that a company had provided to protect their employees. Hence, every year a company will allocate a budget for the medical expenses that spend on their employees. Unfortunately, many companies don't have a system to help them keep track of these expenses. The filing records are not arranged and the management find very difficult to do decision making on the aspect of medical expenses budget. PDS, a distributed system is a solution to all the problem that exists above. The PDS have functionalities on keep all the records of the employees, company approved Hospital, clinics information and panel doctors information in the company database that been create specialize to meet the company needs. Other tools that are available include tools to manage the amount of user, and to change password. In addition, the PDS helps the top management to do the decision making with several reports generated by the system. The reports of PDS are generate by the system using the data in the database and have been analyze accurately and correctly by the system. Basically, the PDS comprises 8 modules and each module has it's own functionalities. There arc 2 categories of users in PDS which is normal users (mostly use by the data entry clerks) and super users (administrator). Conceptually, some functionality will be hide for normal user view. This is to protect the confidential information in the database. ETS is developed using Visual Basic technologies running on Microsoft Windows NT Server 4.0 platform-utilizing database created and stored using SQL Server 6.0.